Examining Organizational Commitment And Workplace Culture On Self-Reported Performance - Rita Sobariah; SeTin SeTin; Lidya Agustina (COMPETITIVE, 2026)
This study aims to examine the relationship between organizational commitment, workplace culture, and employees’ self-reported performance in pharmaceutical distributor companies facing strict drug price control policies in Indonesia. Regulatory pressures in this sector demand high operational efficiency while simultaneously challenging employee motivation and performance, making internal organizational factors increasingly critical. A quantitative approach was employed using survey data collected from 100 marketing employees of pharmaceutical distributor companies in West Java, selected through purposive sampling with a minimum of two years of work experience. Data were analyzed using PLS-SEM. The results indicate that organizational commitment has a strong and significant positive effect on workplace culture (β = 0.598, p < 0.001). Workplace culture also positively and significantly influences self-reported performance (β = 0.351, p < 0.01). However, the mediating effect of workplace culture on the relationship between organizational commitment and self-reported performance is negative yet significant (β = −0.139, p < 0.05), suggesting that an overly rigid or demanding workplace culture combined with high organizational commitment may unintentionally reduce employees’ perceived performance. The model explains 35.9% of the variance in workplace culture and 60.5% of the variance in self-reported performance. These findings highlight the importance of balancing strong organizational commitment with a flexible and supportive workplace culture. Practically, management should avoid excessive cultural rigidity and instead foster adaptive work environments that sustain employee motivation and performance under regulatory uncertainty.